The Effect of PBL Model on Students' Critical Thinking Ability in View of Adversity Quotient (AQ) - Suci, Antonynio; Kamid, Kamid; Yantoro, Yantoro (Journal of Educational Sciences, 2025)
This study aimed to examine the effect of the Problem Based Learning (PBL) model on the critical thinking skills of class XII students at SMAN 3 Tanjung Jabung Timur, as viewed from their Adversity Quotient (AQ). This research employed a quasi-experimental design with two groups: a control group that received conventional learning and an experimental group that received PBL. Data were collected through pretest scores, posttest scores, and an AQ questionnaire. Data analysis was performed using independent samples t-tests and Pearson correlation, with SPSS version 27. The results indicated a significant effect of the PBL model on enhancing students' critical thinking skills (p-value = 0.002; Cohen's d = -0.852). Students in the PBL group demonstrated higher critical thinking skills compared to those in the control group. However, there was no significant relationship between AQ and students' critical thinking skills (r = -0.166; p-value = 0.221). These findings suggest that the PBL model is effective in improving students' critical thinking skills, although AQ did not directly moderate this effect.